How Does the STEM-PjBL e-Book Impact Students' Creative Thinking and Digital Literacy Skills? - Anastasia Novianti Manalu; Insih Wilujeng (Yayasan Keluarga Guru Mandiri, 2025)
Current learning developments are adapted to society's needs, which have developed and entered the 21st century. Creative thinking abilities and digital literacy are 21st-century competencies that students need to develop. This study investigates the impact of an e-book STEM-PjBL on seventh-grade students' creative thinking skills and digital literacy. The research employs a quantitative approach using a one-group pretest-posttest design involving a sample of 32 students selected through random sampling at one of Sleman's public junior high schools. The study utilizes a creative thinking test and a digital literacy questionnaire to assess students' skills before and after the intervention. This research highlights the importance of innovative teaching materials in enhancing students' learning experiences and outcomes. The findings reveal that the STEM-PjBL e-book enhances students' creative thinking abilities, with gain scores categorized as moderate across the aspects of Fluency (0.45), flexibility (0.38), and novelty (0.60). Additionally, students' digital literacy is positively impacted, with the aspect of using skills rated as